Model bilateral agreement for the academic year 2007/2010 Socrates programme: higher education Erasmus Universidade Lusíada de Lisboa and Universidad Francisco de Vitoria - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within Socrates programme. - Subject area: Law, Business studies, Management science.